2020
DOI: 10.1021/acs.nanolett.9b04058
|View full text |Cite
|
Sign up to set email alerts
|

Double Moiré with a Twist: Supermoiré in Encapsulated Graphene

Abstract: A periodic spatial modulation, as created by a moiré pattern, has been extensively studied with the view to engineer and tune the properties of graphene. Graphene encapsulated by hexagonal boron nitride (hBN) when slightly misaligned with the top and bottom hBN layers experiences two interfering moiré patterns, resulting in a so-called super-moiré (SM). This leads to a lattice and electronic spectrum reconstruction. A geometrical construction of the non-relaxed SM patterns allows us to indicate qualitatively t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(58 citation statements)
references
References 39 publications
1
57
0
Order By: Relevance
“…These coexisting moiré patterns with different wavelengths should, in principle, interfere, resulting in a second-order (composite) moiré pattern, as reported in experimental (38)(39)(40) and theoretical studies (41,42). From the two SDPs, we calculated the corresponding twist angles to be 0.24° and 0.38° (see Materials and Methods).…”
Section: Discussionmentioning
confidence: 92%
“…These coexisting moiré patterns with different wavelengths should, in principle, interfere, resulting in a second-order (composite) moiré pattern, as reported in experimental (38)(39)(40) and theoretical studies (41,42). From the two SDPs, we calculated the corresponding twist angles to be 0.24° and 0.38° (see Materials and Methods).…”
Section: Discussionmentioning
confidence: 92%
“…To quantitatively analyse them, a phenomenological model was given, which, for simplicity, assumes that the −4 n 0 filling corresponds a fixed h-BN/graphene moiré with a smaller twist (wavelength L α ), and all extra peaks are from another moiré with a larger twist (wavelength L β ). Thus, one can then extract and fix L α , and solve L β using the formula 17 , 23 where a is graphene’s lattice constant, l β is the reciprocal lattice vector of L β , and δ is the lattice mismatch between graphene and h-BN 24 . Experimentally, L α can be larger than the theoretical maximum of 13.8 nm in a graphene/h-BN superlattice, due to possibly existing strains in the heterostructures 17 , 25 .…”
Section: Resultsmentioning
confidence: 99%
“…Experimentally, L α can be larger than the theoretical maximum of 13.8 nm in a graphene/h-BN superlattice, due to possibly existing strains in the heterostructures 17 , 25 . The above-mentioned analytical formula yields six solutions at each side of the charge neutrality, because of the six vectors formed by the two of moiré Brillouin zone from top and bottom surfaces of graphene 17 , 23 . With this method, one can have access to the relatively precise twist angles in measured samples via their resistive peaks in the field-effect spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavily corrugated Moiré in gr/Ru(0001) shows localized states close to the Fermilevel 19 . It has been shown that lattice relaxation, (which leads to a corrugated surface) is an important parameter to understand the origin of the gap 20,21 and flat-band formation 22 in gr/h-BN systems. The importance of the relaxation was also pointed out for low angle twisted bilayer graphene (TBLG), where an energy gap of up to 20 meV opens at the superlattice subband edge 18,23 , which is also found in experiments 15,24 and is needed to fully describe the Mott-physics of the system.…”
Section: Introductionmentioning
confidence: 99%